رتبة المفعول به في "شعر قبيلة همدان وأخبارها في الجاهلية والإسلام" - دحام، نضال حسن صيوان; صحن، أحمد رسن (جامعة البصرة - مركز دراسات البصرة والخليج العربي, 2023)
تناول الباحث مفهوم الرتبة في (شعر قبيلة همدان وأخبارها في الجاهلية والإسلام) المتمثلة في رتبة المفعول به داخل الجملة وعلاقته بالفعل والفاعل وباقي مكونات الجملة من المفعولات. فالتقديم والتأخير لا يأتي في الجملة عشوائياً أنما يكون لغرض بلاغي يعمد إليه المتكلم، وهو أكثر ما يكون في الشعر منه في النثر. قسمت الرتبة إلى: الرتبة المحفوظة "الثابتة، والرتبة غير المحفوظة" غير الثابتة"، فهي من المسائل التي قصدها وعني بها البلاغيون والنحاة، فتقديم ألفاظ الكلام بعضها على بعض دون المضاف إليه يعد من طرائق العرب في النظم اللفظي في اللغة العربية الفصحى عند العرب. The researcher discusses the concept of object position in "The Poetry of the Hamdan Tribe and its Stories in the Pre-Islamic and Islamic Eras." This concept refers to the placement of the object within the sentence and its relationship with the verb, subject, and other sentence components. The order of words in a sentence is not random but serves a communicative purpose intended by the speaker. This purpose is more prominent in poetry than in prose. The researcher divides the object position into two categories: preserved (fixed) object position and non-preserved (variable) object position. This distinction has been a subject of interest for rhetoricians and grammarians. Placing words in a certain order without attaching them to the object is one of the techniques employed by the Arabs in the linguistic structure of Classical Arabic.
Keywords: الآدب العربي -- الشعر العربي -- الرتبة المحفوظة -- القصائد والدواوين -- النحو العربي